Assessment of the AHRQ Patient Safety Initiative Final Report-Evaluation Report IV - Farley, Donna O. (RAND Corporation, 2008)
Updates the policy context of the Agency for Healthcare Research and Quality (AHRQ) patient safety initiative; documents the current priorities and activities undertaken; and assesses contributions of funded projects and dissemination actions to support adoption of evidence-based safe practices. Discusses implications for future AHRQ policy, programming, and research; suggests ways to strengthen AHRQ activities.